2020
DOI: 10.4314/njt.v39i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of displacement models for modular horizontal wind turbine blade structure

Abstract: This study examined the normal, radial, axial and tangential loading cycles undergone by wind turbine rotor blades and their effects on the  displacement of the blade structure. The rotor blade was modelled using Q Blade finite element sub module, which evaluated the loading cycles in  terms of the forces induced on the blade at various frequencies through several complete revolution cycles (360o each cycle). At frequencies of 5 HZ, 23 Hz, 60 Hz, 124 Hz and 200 Hz, maximum strain deformation of 0.004, 0.04, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…are required to meet the basic needs of man which are food, clothing and shelter. For example, sunlight (solar energy) is required for plant growth, electrical energy obtained from hydropower or fossil fuels (crude oil) are also needed for power generation at homes and industries [3]. Studies have shown that less than 10% of the population of 21 Sub-Saharan African countries, have access to sufficient electricity supply, showing that there is need for alternative sources of energy particularly in the African settlements [4].…”
Section: Introductionmentioning
confidence: 99%
“…are required to meet the basic needs of man which are food, clothing and shelter. For example, sunlight (solar energy) is required for plant growth, electrical energy obtained from hydropower or fossil fuels (crude oil) are also needed for power generation at homes and industries [3]. Studies have shown that less than 10% of the population of 21 Sub-Saharan African countries, have access to sufficient electricity supply, showing that there is need for alternative sources of energy particularly in the African settlements [4].…”
Section: Introductionmentioning
confidence: 99%
“…A wind turbine is a rotating mechanical device that converts kinetic energy of fast moving winds into electrical energy. The central shaft is connected to the wind turbine generator which converts the rotary motion of the output shaft into electrical power [2,3]. All living things in one way or the other depend on energy for survival, and modern civilization will continue to thrive only if existing sources of energy can be developed to meet the growing world's demand [4,5].…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%
“…Studies have shown that wind turbine rotor blades are subjected to high fatigue cycle and vibrational frequency that can expose the blades to failure during rotation if proper monitoring and control devices are not installed [20], and also subjected to a wide range of loads such as flapping, tension and compression, twisting etc, all induced by the rotational movement and variable aerodynamic loads. The rotor shaft is subjected to loading conditions such as torsion, bending, and sometimes axial loading [21,22].…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%